Effects of Acute L-Carnitine Supplementation on Lipid Peroxidation and Nitric Oxide Level - Atalay Guzel, Nevin; Coskun, Sule; Eroglu, Huseyin; Yilmazoglu, Kadriye; Senel, Omer (Asian Journal of Chemistry, 2010)
The purpose of this study was to determine the effects of acute Lcarnitine supplementation on blood malondialdehyde (MDA) level as a marker of lipid peroxidation and nitric oxide (NO) level. With this aim, 8 male and 8 female total 16 national badminton players participated into this study voluntarily. Astrand protocol was used to determine the maximal oxygen consumption. Each subject received an acute dose (2 g L-carnitine before 1 h of exercise) and placebo in a randomized, doubleblind crossover design. Dietary intake and exercise were replicated for 4 d prior to each trial. Blood samples were drawn by venipuncture before and immediately after exercise. No significant differences were found between measurements of with and without L-carnitine supplementation of participants as regards to all measured parameters. The result of this study shows that acute L-carnitine supplementation before 1 h of the exhaustive exercise does not affect lipid peroxidation and nitric oxide levels.